The particle filter algorithm: parallel implementations and performance analysis over Android mobile devices. (14th August 2015) - Acosta, A.; Almeida, F.
Summary: The advent of emergent system on chip and multiprocessor system on chip opens a new era on the small mobile devices (smartphones, tablets, etc.) in terms of computing capabilities and applications to be addressed. Given the ability of these devices to interact with the real world through the camera, the development of efficient algorithms related to image processing and computer vision is mandatory. The particle filter algorithm is an algorithm frequently used in image and video processing; it constitutes the baseline algorithm in many applications: feature tracking, facial recognition, tracking of vehicles in traffic, video compression and so on. We propose a parallel implementation for the particle filter algorithm oriented to mobile Android devices. Three different versions of this algorithm are presented: a Java sequential implementation and two Renderscript parallel versions, an ad hoc implementation and a parallel implementation generated automatically with Paralldroid. The results obtained by the parallel versions over different Android platforms present high accuracy with a high processing rate of frame per second and a high speedup at the same time. Copyright © 2015 John Wiley & Sons, Ltd.